The Effect Of Reminiscence Therapy On Cognitive Function In The Elderly In Abiansemal 1 Public Health Center On 2018. - IGA HARINI (Jurusan Keperawatan Poltekkes Kemenkes Denpasar, 2018)
The purpose of this study was to determine the effect of reminiscence therapy on cognitive function in elderly in UPT. PuskesmasAbiansemal 1 year 2018. The research design used was pre experimental with one-group pre-post test and used purposive sampling method with 14 respondents. Instrument of data collection in this research is general cognitive test using MMSE. Result of the research, the cognitive function score before all treatments were given in the category of mild cognitive impairment that is 14 people (100%) and after being treated in the category of mild cognitive impairment 13 persons (92.9%). The result of non parametric test by using Wilcoxon signed rank test on cognitive function value before and after given reminiscence therapy get significant value p = 0,023 (p0,050). The conclusion that giving reminiscence therapy affects cognitive function in elderly